2018
DOI: 10.1182/bloodadvances.2018016295
|View full text |Cite
|
Sign up to set email alerts
|

Lineage tracing of murine adult hematopoietic stem cells reveals active contribution to steady-state hematopoiesis

Abstract: Key Points HSCs contribute robustly to steady-state hematopoiesis. Platelets receive extensive influx from HSCs compared with other myeloid or lymphoid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 35 publications
7
73
1
Order By: Relevance
“…This approach does not exclude additional feedback loops from progenitor and peripheral blood compartments (as pursued in other works, for example [65,66]), but demonstrates that HSC heterogeneity is a potential mechanism to explain the limited recovery of highly potent rpHSCs to targeted depletion of certain hematopoietic cell types [8]. Although our assumption might oversimplify a more complex regulation, our approach emphasizes a regulatory control mechanism below the rpHSC compartment that links continuous hematopoietic output with a rare activation of the rpHSC reservoir and is in agreement with a set of recent experimental findings [5,6,11]. In fact, coupling rpHSC turnover to the demand of mtHSCs is sufficient to explain a diverse set of phenomena.…”
Section: Stem Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…This approach does not exclude additional feedback loops from progenitor and peripheral blood compartments (as pursued in other works, for example [65,66]), but demonstrates that HSC heterogeneity is a potential mechanism to explain the limited recovery of highly potent rpHSCs to targeted depletion of certain hematopoietic cell types [8]. Although our assumption might oversimplify a more complex regulation, our approach emphasizes a regulatory control mechanism below the rpHSC compartment that links continuous hematopoietic output with a rare activation of the rpHSC reservoir and is in agreement with a set of recent experimental findings [5,6,11]. In fact, coupling rpHSC turnover to the demand of mtHSCs is sufficient to explain a diverse set of phenomena.…”
Section: Stem Cellssupporting
confidence: 89%
“…In fact, regeneration of the hematopoietic system after cell transplantation into an irradiated host is still considered to be the gold standard for a functional definition of HSCs. Minimally invasive methods for marking of HSCs [5][6][7][8][9][10][11][12][13][14][15] recently allowed studying the hematopoietic system in unperturbed, that is, not transplanted, settings, thereby adding new insights into the functional role of HSCs and their progenitor populations. Based on these new findings, it appears that multipotent progenitors (MPPs) ensure the long-term supply with functional, differentiated hematopoietic cells in the homeostatic situation, while rarely depending on the turnover of the HSC population.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies that also utilized noninvasive labeling methods support a more active role for HSCs in native hematopoiesis [83−86]. Induced labeling in Pdzk1ip1 + adult murine HSCs-a serially transplantable HSC population less prone to mobilization-suggested that these cells give rise to other HSCs, as well as progenitors and mature blood cells, and were the main drivers of native hematopoiesis [83,85,86]. Using the Polylox barcoding system in adult murine Tie2 + HSPCs, Pei et al .…”
Section: Normal Agingmentioning
confidence: 99%
“…Assessing the HSPC dynamics in an unperturbed BM environment directly in humans represents a methodological challenge. In vivo color labeling and transposase-based inducible systems have been used to estimate the replication rate of murine HSCs [26][27][28][29] in vivo. These experimental settings are mostly inapplicable to humans.…”
Section: In Vivo Dynamics Of Human Hsc In Unperturbed Systemmentioning
confidence: 99%
“…Although previous studies of unperturbed hematopoiesis in mice suggested that hematopoiesis was predominantly sustained by MPPs, 26,27 several publications exploiting numerous in vivo labeling systems have now proven that murine adult HSCs robustly contributed to steady-state hematopoiesis. 18,28,29 The exploitation of somatic mutations in humans has led to the proposal that phenotypically defined HSCs actively contribute to steady-state hematopoiesis also in humans ( Figure 2). This conclusion, together with the data on transplanted human HSPC discussed below, adds a new frame of reference for future data interpretation.…”
Section: Hematopoiesis After Transplantationmentioning
confidence: 99%